FRI0323 Prospective Follow-Up of Tocilizumab Treatment in 1503 Patients with Refractory Rheumatoid Arthritis: Tolerance Data at 1 Year from the French Registry Regate (Registry – Roactemra). (10th June 2014) - Morel, J.; Duzanski, M.O.; Flipo, R.M.; Cantagrel, A.; Combe, B.; Dougados, M.; Mariette, X.; Gottenberg, J.E.; Soubrier, M.; Vittecoq, O.; Saraux, A.; Schaeverbeke, T.; et al.
Abstract : Objectives: To assess tolerance and safety of rheumatoid arthritis (RA) treatment by tocilizumab (TCZ) in real life Methods: The French Society of Rheumatology set up the REGATE registry to prospectively collect, at 3 months and then every 6 months for 5 years, data from 1500 patients treated with TCZ for refractory rheumatoid arthritis. Results: From January 13th 2011 to June 19th 2013, RA patients treated by TCZ initiated after January 1st 2010 have been prospectively included from 78 French centres in the REGATE registry. Among the 1503 included patients (women: 80%, mean age 56.6±13.6 years, mean disease duration: 14.2 years (±10), mean number of prior DMARD: 2.4 (±1.5), 85.2% RF-positive, 81.6% ACPA positive), 5.25% of patients had a history of cancer and 5% of severe infection, 19% of cardiovascular events and 22% of dyslipidemia before TCZ. 20% had not received any anti-TNF prior to TCZ and the mean number of biologics before TCZ was 2±1.5. The last biologic prescribed before initiation of TCZ was an anti-TNF for 59.7% of patients, rituximab for 17%, abatacept for 13.4%. The median time between the last dose of the previous biologic and the first infusion of TCZ was 1.64 months (0-120). Before TCZ, mean DAS28 was 5.1±1.4. 69% of the patients received steroids with a mean dose of 11±24 mg/day. 60% of patients were treated with and a concomitant DMARD, mainly methotrexate (79.4%). After 1.3 years, the drug was stopped for 206 patients: 61 of them (31%) for primary inefficacy, 35 (17, 8%) for secondary inefficacy, 71 (36%) for safety reasons. 1048 patients have already had at least 1 follow-up visit with mean current follow-up duration of 11.8 (±7.4) months corresponding to an exposure of 1052 patient/years (PY). Fifty five severe infections (mainly soft tissues and respiratory tract with respectively 32% and 27%) were reported in 49 patients corresponding to a rate of severe infections of 5.2/100 PY. The other SAE were 3 lymphoma (0.3/100 PY), 7 cancer (0.65/100 PY), eight thromboembolic events (0.7/100 PY), eight infusion reactions with definitive withdrawal of TCZ (0.7/100 PY) and one cardiovascular event (0.1/100 PY). Six perforations of bowel were observed (0.6/100 PY) and 5 out 6 patients were treated with steroids. Three deaths were recorded: one septic chock, one pneumocystosis, and one hypertrophic cardiopathy. Conclusions: These results of the REGATE registry show that a high proportion of patients treated with TCZ as first line of biologic (20%) and in monotherapy (40%) in outpatient car. Severe infections are close to rates observed in pivotal studies (1). Perforation of bowel is 3 times higher compared to extension studies but steroids combined with TCZ may explain this result. References: Genovese MC et al. J Rheumatol. 2013;40:768-80 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5093